2014
DOI: 10.24084/repqj12.347
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of the Hydrodynamic Performance of Horizontal Axis Marine Current Turbines Using a Panel Method Program

Abstract: The marine current turbine is the mechanical device that captures the kinetic energy of marine current to generate electrical power. This paper presents the application of an academic panel code based on potential flow theory for the analysis of marine current turbines. The aim of this work is also to analyze the effect of the addition of a duct on the hydrodynamic performance of the turbine. The numerical results show that the addition of duct improves significantly the efficiency of the turbine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results showed that the speed of the incoming flow in rotor plane of the diffuser augmented turbine was 1.5 timesmore than that of bare turbine. Ait-Mohammed et al [23] observed a significant improvement in the hydrodynamic performance of a marine turbine due to the addition of a duct. The potential theory based panel method was used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the speed of the incoming flow in rotor plane of the diffuser augmented turbine was 1.5 timesmore than that of bare turbine. Ait-Mohammed et al [23] observed a significant improvement in the hydrodynamic performance of a marine turbine due to the addition of a duct. The potential theory based panel method was used for this purpose.…”
Section: Introductionmentioning
confidence: 99%